Indivisibilities in R & D Investment and Transient Leadership in Oligopoly - Flavio Delbono; Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
In this paper we study a one-shot game of R&D between two price-setting firms that are asymmetrically placed as they produce at different cost levels. The R&D technology displays increasing returns in the form of invisibilities. We show that there exists a unique equilibrium in pure strategies, and we prove that the incumbent has never greater probability of winning the patent race than the rival.
Keywords: 330